Toxic emissions from smouldering combustion of woody biomass and derived char with a case study of CO build-up in an ISO container - Nyombi, Antony; Williams, Mike; Wessling, Roland (Taylor & Francis, 2019)
Carbon monoxide (CO) from the use of biomass products causes some deaths in the United Kingdom every year. This study was undertaken to evaluate the amount of CO from five species of wood sawdust, and charcoal with a case study of CO in a confined ISO container. Laboratory experiments were conducted at temperatures between 350°C and 600°C under flowing air. Results showed a strong dependence of CO emissions on temperature and airflow. The CO emissions in the ISO container were above the recommended exposure limits due to poor ventilation.
Keywords: Carbon monoxide; sawdust; charcoal; airflow; confined space; temperature